2016
DOI: 10.1002/em.22018
|View full text |Cite
|
Sign up to set email alerts
|

Individual variations in dose response for spatial memory learning among outbred wistar rats exposed from 5 to 20 cGy of 56Fe particles

Abstract: Exposures of brain tissue to ionizing radiation can lead to persistent deficits in cognitive functions and behaviors. However, little is known about the quantitative relationships between exposure dose and neurological risks, especially for lower doses and among genetically diverse individuals. We investigated the dose relationship for spatial memory learning among genetically outbred male Wistar rats exposed to graded doses of (56) Fe particles (sham, 5, 10, 15, and 20 cGy; 1 GeV/n). Spatial memory learning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…In conclusion, it is understandable that HZE particle exposure is presumed to have a negative influence on some lower and high-level cognitive functions, as many studies support this conclusion 12,14,33,40,98,99 . However, our study shows this is not universally true.…”
Section: Discussionmentioning
confidence: 87%
“…In conclusion, it is understandable that HZE particle exposure is presumed to have a negative influence on some lower and high-level cognitive functions, as many studies support this conclusion 12,14,33,40,98,99 . However, our study shows this is not universally true.…”
Section: Discussionmentioning
confidence: 87%
“…In conclusion, it is understandable that HZE particle exposure is presumed to have a negative influence on some lower and high-level cognitive functions, as many studies support this conclusion (21,23,44,(149)(150)(151) . However, our study shows this is not universally true.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the studies performed in rodents showed a high inter-individual variability in HZE-induced neurobehavioral deficits. In particular, in the low-range dosage, deficits were particularly pronounced in a subgroup of poor-learner animals [43]. This result strongly suggests the involvement of individual genetic factors, although the specific involved loci were not investigated.…”
Section: Effects Of Space-relevant Radiation On Mammalian Cnsmentioning
confidence: 88%
“…Analyses of rodent models have provided the most extensive evidence about the potential neurocognitive complications caused by GCR ( Table 1), which could affect skills critical for missions, as well as long-term neuro-psychological health [8,10,24]. Low doses (5-20 cGy) of 1 MeV/n 56 Fe particles lead to severe deficits of mean spatial memory performance in rats, three months after exposure [42][43][44]. Similar effects where obtained by irradiating rats with low doses of 48 Ti [65], supporting the notion that LET-dependency of neurocognitive impairment may be relatively independent of cell killing.…”
Section: Effects Of Space-relevant Radiation On Mammalian Cnsmentioning
confidence: 99%